Study on Abundance and Distribution Pattern of Collembola on Three Types of Land Utilizations in Banjar Regency, South Kalimantan - Trianto, Manap; Marisa, Fajri (BIO-EDU: Jurnal Pendidikan Biologi, 2020)
Collembola is one of soil organism which classified as mesofauna. This reseach is aims to study the abundance and distribution patterns of Collembola on three types of land utilization in Banjar District, South Kalimantan Province. This research was conducted on April 2020 by using a purposive sampling method. Based on results of Collembola identification obtained at the sampling location, there are 12 genera, 6 families, and 2 orders of Collembola. The highest abundance is found in oil palm plantations. While the Collembola distribution pattern on the three types of land clearing is the same, which is clustering. The results of this study are expected to provide information on the study of abundance and distribution patterns of Collembola in South Kalimantan Province related to environmental factors also help in carrying out sustainable ecosystem development.